The Crime of SQL Injection in the Service System at Bina Insan University Lubuklinggau - Erwinsusanto; Edi Surya Negara (Jurnal Jaringan Komputer dan Keamanan, 2024)
The rapid progress of contemporary technology significantly aids in the execution of work. The internet, as one of the most developed technologies, facilitates communication, access to stored data, and generally simplifies professional tasks. However, this convenience is accompanied by criminal threats targeting internet users, with phishing (or SQL Injection, according to the Indonesian text) being a particularly damaging offense. Phishing is defined as a threat employing social engineering techniques to deceive users by impersonating an authorized entity. This type of attack is prevalent across various industrial sectors, including corporate, banking, and education. Key factors contributing to phishing in online banking services involve users' limited knowledge, psychological vulnerabilities, and social networking privacy issues. Therefore, securing computer networks is essential for the prevention of phishing (or SQL Injection) attacks. This study employs a qualitative research methodology with descriptive techniques.